Project Management Documentation For Mysat Development Process - Othman, Noor Raweyah (Universiti Sains Malaysia, 2019)
The purpose of this thesis is to document the activities related to managing design, analysis, construction, testing, and integration of a qualification and possible flight of Cubesat from USM Space System Lab (USSL) named Malaysia Youth Satellite (MYSAT). This thesis will basically describe the process and result obtained from all the subsystem involve in MYSAT development, including the project cost analysis and scheduling as early as April 2017 for easy view by the project team. Since few subsystem involve including costing and scheduling, there are no system to sort out and organized the information accordingly. Therefore, project management tools have been suggested to help make all the information be in organize manner. As for MYSAT itself the mission is to measure electron density in the ionosphere E-Layer to prove the correlation between the correlation between seismic activity and ionosphere anomaly and the changes of the electron-density. Thus, system engineering and project management tools is used to support the conceptual design of MYSAT. MYSAT small satellite system engineering utilizes a spreadsheet-based approach to efficiently track information regarding the mass, power, and volume of the satellite and satellite subsystems. All information gathered so far will be stored in the Microsoft Excel for detailed view which derived using Work Breakdown Structure (WBS) method. For WBS the method used is by deriving the information into levels and subdivision based on their priorities and arrangement. For instance the information divided into project management part, mission overview part and subsystems part. Therefore, documentation using Microsoft Excel have been develop as for now.